Assistance in Making Nutritional Value Information on Packaging Labels at UMKM Abon Lele "Yu Kaji" - Mardani Rizkia Pramudita; Riski Ayu Anggreini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The packaging label is a description that is represented in the form of words or pictures regarding product information as a means of communication between producers and consumers without having to open the packaging. The government through Law no. 18 of 2012 concerning food requires manufacturers to put a label on the packaging. One of the information that must be included on the label is the nutritional value information label (ING). However, there are still many UMKM players who have not put the ING label on the packaging label, one of them is the UMKM Abon Lele "Yu Kaji". This is due to the lack of awareness of business actors about the importance of ING for consumers to know the measure of food consumed according to body needs. Therefore, this service activity will focus on facilitating partners to produce information on ING of shredded catfish through outreach and mentoring. The result of this dedication is the design of information labels on the nutritional value of shredded catfish and business owners better understanding the importance and benefits of labeling nutritional value information on packaging. With the nutritional value information label, it is hoped that it can prove to consumers that this shredded catfish product has many benefits that are worth buying and makes it easier for producers to obtain a legal distribution permit such as BPOM.